Poliésteres y Reciclaje Químico del Poli(tereftalato de etileno) - Bertolotti, Bruno (2005)
This contribution presents a general review of the chemistry of polyesters. The different alternatives for the production of polyesters with different properties are presented and analyzed. In this respect, the characteristics related to their industrial use are highlighted, as well as their applications. Due to the importance of poly(ethylene terephthalate) in our modern society and its massive use, the most common alternatives for its chemical recycling are detailed. Special attention is given to the depolymerization of poly(ethylene terephthalate), including examples of the work developed by the authors.